Adverse Selection in Durable Goods Markets - Hendel, Igal; Lizzeri, Alessandro (American Economic Review, 1999)
We present a dynamic model of adverse selection to examine the interactions between new and used goods markets. We find that the used market never shuts down, the volume of trade can be large, and distortions are lower than previously thought. New cars prices can be higher under adverse selection than in its absence. An extension to several brands that differ in reliability leads to testable predictions of the effects of adverse selection. Unreliable brands have steeper price declines and lower volumes of trade. We contrast these predictions with those of a model where brands physically depreciate at different rates. (JEL D82, L15)